Training Specialists for the Digital Economy in Orenburg State University - Zh. A. Ermakova (Moscow Polytechnic University, 2019)
The article analyzes the experience of Orenburg State University in the field of training specialists for the digital economy. It describes key competences for the digital economy: hybrid interdisciplinary management skills, team work abilities, skills in the spheres of management in cyberphysical systems, management in institutional changes and options for their generation in the training process of a university. It actualizes the task for universities and employers to coordinate their activities in making up the list of requirements to provide successive development of the digital economy competences. Special focus is given to designing and implementation of an electronic information and educational environment at university, and its characteristics are described. The article highlights the use of new format learning materials to meet the challenges of the digital economy in the fields of engineering, construction, computer safety, management.